Analysis of Prospects For The Development of The Rita Tourism Park on Community Income In Bonto Kanang Village, District Takalar - Nahriana Nahriana; Ratnah S (International Journal of Economics, Business and Innovation Research, 2024)
The development of tourist objects is often considered as a way to deal with various economic problems in Indonesia. Low and lame economic growth and development can be overcome by the tourism industry, because the existence of the tourism industry can create new jobs and provide many economic opportunities. This research was conducted at Rita Tourism Park in Bonto Kanang Village, Kec. Galesong Kab. Takalar with 45 respondents. The type of research used in this research is quantitative research. From the results of the study it can be seen that the Rita Tourism Park plays a very important role in improving and increasing the community's economy, providing new job opportunities so that it can reduce unemployment. Development around the tourism sector involves the role of government and local communities. With the development of tourism that is more creative, it is able to attract many tourists to visit this Rita Tourism Park. With so many tourists coming to visit, it will have an impact on increasing people's income, especially the people in Bonto Kanang Village, Galesong District, Takalar Regency.